A randomized controlled trial of cardiac resynchronization therapy in patients with prolonged atrioventricular interval: the REAL-CRT pilot study. Issue 2 (13th November 2019) - Botto, Giovanni Luca; Iuliano, Assunta; Occhetta, Eraldo; Belotti, Giuseppina; Russo, Giovanni; Campari, Monica; Valsecchi, Sergio; Stabile, Giuseppe
Abstract: Aims: A prolonged PR interval is known to be associated with increased mortality and a higher risk of developing atrial fibrillation (AF). We tested the hypothesis that cardiac resynchronization therapy (CRT) is superior to conventional dual-chamber pacing with algorithms for right ventricular pacing avoidance (DDD-VPA) in preserving systolic and diastolic function and in preventing new-onset AF in patients with normal systolic function, indication for pacing and prolonged atrioventricular conduction (PR interval ≥220 ms). Methods and results: We randomly assigned 82 patients with ejection fraction >35%, indication for pacing and PR interval ≥220 ms to CRT or to DDD-VPA. On 12-month follow-up examination, the study and control arms did not differ in terms of left ventricular end-systolic volume (44 ± 17 mL vs. 47 ± 16 mL, P = 0.511) or ejection fraction (55 ± 6% vs. 57 ± 8%, P = 0.291). The E to A mitral wave amplitude ratio was higher in the CRT arm (1.3 ± 1.3 vs. 0.8 ± 0.4, P = 0.046) and the E wave deceleration time was longer (262 ± 83 ms vs. 205 ± 51 ms, P = 0.027). Left atrial volume was smaller in the CRT arm (64 ± 17 mL vs. 84 ± 25 mL, P = 0.035). Moreover, the functional class was lower in CRT patients (1.4 ± 0.6 vs. 1.8 ± 0.5, P = 0.010). During follow-up, CRT was associated with a lower risk of new-onset AF [hazard ratio = 0.37 (0.13–0.98), P = 0.046]. Conclusion: Cardiac resynchronization therapy proved superior to DDD-VPA in terms of better diastolic function, less left atrial enlargement and lower risk of new-onset AF, at 12 months. These data need to be confirmed in a larger trial with longer follow-up. Clinical trial registration: URL: http://clinicaltrials.gov/ Identifier: NCT02150538